University Governance and Dean’s Leadership in Improving Lecturer Performance - Mulyadi, Edi; Suhaya, Suhaya; Dahlan, Jarnawi Afgani (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
Research is based on the idea that university governance and the dean's leadership are very important for improving lecturer performance. This study aims to analyze the effect of university governance and the dean's leadership on the performance of lecturers at the Islamic University of Sheikh-Yusuf (UNIS).. The study uses a quantitative approach with correlation and regression analysis techniques. The sample size of the study was 40 lecturers taken using proportional stratified random sampling. The research gives the result that there is a positive and significant influence on the university governance on the performance of lecturers at the Islamic University of Syekh-Yusuf. University governance has a positive and significant effect of 71.06% on the performance of lecturers; dean leadership has a positive and significant effect of 16.40% on lecturer performance, and together there is a positive and significant effect of university governance and dean's leadership of 73.59% on the performance of lecturers at the Islamic University of Syekh-Yusuf.